FORENSIC EVIDENCE AS A MEAN OF PROOF IN DEVELOPING PRIMA FACIE CASE IN TAKHBIB CRIMINAL OFFENCE (UUM Journal of Legal Studies, 2022)
A third party’s intervention has been one of the most significant factors in Malaysian divorce cases. Third parties may come from family members and non-family members. This interference is called takhbīb. Within the scope of Malaysian Syariah criminal law, tahkbib is regarded as a criminal offence. However, it is difficult to prove this criminal offence. None of the Syariah law journals reported cases that could be used as reference or case studies. This article proposes a method of proof, which is practical and can be carried out in the Syariah courts to prove the criminal offence of takhbīb. In gathering and compiling the necessary data and related materials, this qualitative study embraced document analysis as a research method. These data are inductively evaluated by implementing qualitative content analysis. This study showed several obstacles in the development of a prima facie prosecution by the Syarie Public Prosecutor, including the absence of eyewitnesses present as evidence. Third-party intrusion is commonly committed through social networks such as WhatsApp, Telegram, WeChat, and Facebook Messenger. The use of such media networks as a medium of contact may also be brought as part of the evidence before the Syariah courts. The best mechanism to beimplemented in this case is by using digital forensics and expert opinion. The digital forensic investigator will track or archive the communications from the social media, and deliver them in the form of a written text. In terms of proving the commission of takhbīb criminal offence, this study contributes to the improvement of the Syariah legal system. In short, the law still provides a method of proving criminal offences. Any legal practitioner should make good use of statutory provisions instead of suggesting amendments to it.